ANALISIS STRUKTUR ALUR KUMPULAN CERPEN ROBOHNYA SURAU KAMI KARYA AA. NAVIS - Jupon, Rara Marselina (STIT AL MULTAZAM, 2020)
Literature is the work of human creations to express their experiences through language, both orally and in writing that can cause a sense of beauty and can thrill the readers, besides that literature is also born of a cultural situation, not because of cultural emptiness, literature was born to realize the culture itself in its own way. A collection of short stories